DETERMINATION OF LEAKS IN THE MAIN: PIPELINE BY “PRESSURE WAVE” - Fokeeva, Liya; Zainyllina, Vilena (Revista Inclusiones, 2019)
This paper describes a method for determining the coordinates of leakage and mass flow, based on the change in pressure over time in the cross-section of the linear part of the main pipeline. Two possible cases of pressure drop are considered: with constant pressure at the end of the pipeline and with a changing pressure at the end of the pipeline. Based on a mathematical model describing the flow of a fluid in a pipeline with leakage, as well as using the Fourier transform, parameters of the oil product and the pipeline, calculation formulas were obtained to determine the parameters of the leakage from the pipeline.